2019
DOI: 10.3389/fimmu.2019.02319
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 as Biomarker for Acute GvHD and Survival After Allogeneic Transplant With Post-transplant Cyclophosphamide

Abstract: Background: Although the outcome of allogeneic hematopoietic stem cell transplantation (allo-HSCT) has dramatically improved in the past decade, it is still compromised by transplant-related mortality (TRM), mainly caused by Graft-vs. -Host Disease (GvHD).Methods: We conducted a prospective observational study to ascertain the potential of serum interleukin-6 (IL6) levels, measured before conditioning and 7 days after allo-HSCT, in predicting acute GvHD, TRM and survival after allo-HSCT with Post-Transplant Cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 47 publications
3
18
0
Order By: Relevance
“…Increased proportion in severe COVID-19 (11,12) IL-6 High level in post-transplant period (13,14) High level in severe COVID-19 (15-17) lymphocytopenia…”
Section: Allohsct Covid-19 Symptomatic Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased proportion in severe COVID-19 (11,12) IL-6 High level in post-transplant period (13,14) High level in severe COVID-19 (15-17) lymphocytopenia…”
Section: Allohsct Covid-19 Symptomatic Casesmentioning
confidence: 99%
“…Among alloHSCT receiving patients, those with high pre-transplant levels of IL-6 have higher frequency of transplant-related mortality as compared to their counterparts ( 13 ). This observation is supported by the genetic data showing that IL-6 G allele carriers have higher levels of IL-6 in the blood during the post-transplant period and if transplanted from a donor homozygous for the IL-6 G allele are at a high risk of severe aGvHD ( 14 , 112 , 113 ).…”
Section: Lymphocytes and Monocytes In The Pro-inflammatory Environmentmentioning
confidence: 99%
“…Elevated levels of C20-OH/C18-DC and C22 at baseline (pre-HCT) were also associated with worsened OS and elevated levels of C18:1 and C18:2 were associated with increased cGVHD. Furthermore we found that baseline levels of several inflammatory markers previously linked to worsened HCT outcomes (including TNF-a [ 40 ], IL12/p70 [ 41 ], IL-6 [ 42 ], and IL22 [ 43 ]) were associated with decreased survival. Pre-HCT levels of REG3A in the pasireotide group (implicated as a marker for GI GVHD [ 44 , 45 ]) were also associated with the development of chronic GVHD.…”
Section: Discussionmentioning
confidence: 97%
“…When comparing pre-HCT to post-HCT (D14) samples, changes in MIP-1a, MIP-1b, TNF-a, IL-8.Pro, and IL-6, were associated with increased risk of death in our sample (HR 1.16, 8.71, 2.64, 6, and 1.38 respectively, with p<0.05). Furthermore in the pasireotide group, pre-to-post-HCT changes were noted in markers previously associated with transplant outcomes including GVHD (with increases in CRP [ 46 , 47 ], SAA [ 48 ], IL7 [ 49 ], TSLP [ 50 ], PlGF [ 51 ], IL6 [ 42 ], IL27 [ 52 ], TNFR1 [ 53 ], IL1RL/ST2 [ 54 ], MMP3 [ 55 ], TNFRII [ 56 ] and decreases in bFGF [ 57 ], IL12/p70 [ 41 ], IL6Ra [ 58 ], and Paraoxonase [ 48 ]), non-relapse mortality (D-Dimer [ 59 ]) and OS (Il1RL/ST2) [ 60 ]. Differences in sample size and collection media restricted our ability to compare inflammatory and metabolomics profiling between pasireotide and controls, however the associations and references listed above in the pasireotide group are consistent with prior reports of the prognostic relevance of inflammatory and metabolic markers in HCT.…”
Section: Discussionmentioning
confidence: 99%
“…ASCT allogenic stem cell transplantation, CHDF continuous hemodiafiltration, IL-6 interleukin 6 with ASCT-induced complications and are prognostically relevant [12]. Although little is known about the connection between messenger profiles and success of stem cell transplantation, elevated levels of several cytokines, such as members of the IL-6 family before and after ASCT could increase the risk of Graft-versus-host-disease and transplantrelated mortality [13]. While the exact etiology of hyperinflammation in the case of this patient may be multifactorial, we presume that Anti-Thymocyte-Globulin (ATG) will have significantly contributed to cytokine release.…”
Section: Discussionmentioning
confidence: 99%